The Job Perception Inventory: considering human factors and needs in the design of human–AI work - Berretta, Sophie; Tausch, Alina; Peifer, Corinna; Kluge, Annette (Frontiers in Psychology, 2023)
Artificial intelligence (AI) is seen as a driver of change, especially in the context of business, due to its progressive development and increasing connectivity in operational practice. Although it changes business and organizations vastly, the impact of AI implementation on human workers with their needs, skills, and job identity are less considered in the development and implementation process. Focusing on humans however enables unlocking synergies as well as desirable individual and organizational outcomes. The objective of the present study is a) to develop a survey-based inventory from literature on work research and b) a first validation with employees encountering an AI application. The Job Perception Inventory (JOPI) functions as a work-analytical tool to support human-centered implementation and application of intelligent technologies. It is composed of established and self-developed scales, measuring four sections of work characteristics, job identity, perception of the workplace and the evaluation of the introduced AI. Overall, the results from a first study from a series of studies presented in this article indicate a coherent survey inventory with reliable scales that can now be used for AI implementation projects. Finally, the need and relevance of the JOPI is discussed against the background of manufacturing industry.